ANALYSIS OF INDIVIDUAL CHARACTERISTICS AND WORK ETHIC ON EMPLOYEE PERFORMANCE WITH WORK ENVIRONMENT AS AN INTERVENING VARIABLE AT THE REGIONAL FINANCE AND ASSET AGENCY OF NORTH SUMATRA PROVINCE - Eka Gunawan Putra; Elfitra Desy Surya; Mesra B (RADJA PUBLIKA, 2024)
This study aims to analyze the influence of individual characteristics and work ethic on employee performance with the work environment as an intervening variable at the Regional Finance and Asset Agency of North Sumatra Province. This study uses a quantitative approach with a survey method by distributing 80 questionnaires to employees as respondents. The sample determination was carried out using a purposive sampling technique so that the data obtained was in accordance with the research needs. Data analysis was carried out using path analysis to see the direct and indirect effects between variables. The results of the study showed that individual characteristics have a positive but insignificant effect on employee performance but have a positive and significant effect on the work environment. Work ethic has a positive and significant effect on the work environment as well as on employee performance. The work environment has a positive and significant effect on employee performance. Thus, the work environment acts as an intervening variable that mediates the influence of individual characteristics and work ethic on employee performance. The results of this study are expected to be a consideration for leaders in improving employee performance through the development of individual characteristics, instilling a good work ethic, and creating a conducive work environment.